Role of LncRNAs in the Epithelial-Mesenchymal Transition in Hepatocellular Carcinoma - Ge, Xiaoyong; Yao, Yuan; Li, Jing; Li, Zhaonan; Han, Xinwei (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a type of primary liver cancer with a high incidence and mortality rate. HCC develops insidiously, and most newly diagnosed cases are in the middle and advanced stages. The epithelial-mesenchymal transition (EMT) is a vital mechanism underlying metastasis in patients with advanced HCC. EMT is a multistep and complex procedure. The promotion and inhibition of EMT directly affect the migration and invasion of HCC. LncRNAs are involved in the epigenetic modification of genes, regulation of gene transcription, and posttranslational modification of proteins. LncRNAs also play important roles in regulating EMT progression in HCC and are promising biomarkers and therapeutic targets. This review focused on summarizing the mechanism by which lncRNAs regulate EMT in HCC. In particular, lncRNAs were reported to primarily act as RNA sponges, and the regulation of EMT involves major signaling pathways. Finally, we reviewed the mechanisms by which lncRNAs are involved in drug resistance and discussed the clinical prospects and potential challenges of utilizing lncRNAs to treat HCC.